Case report: A systematic approach for the forensic evaluation of child abuse: lessons from a complex case - Di Lorenzo, Pierpaolo; Capasso, Emanuele; Sammarco, Anita; Pieri, Maria; Casella, Claudia (Frontiers in Psychiatry, 2026)
Child abuse (CA) remains a significant public health concern, where distinguishing between accidental and intentional injury is particularly difficult in complex cases involving underlying medical conditions. We present a disturbing case study of severe abuse and neglect to illustrate the necessity of a systematic and evidence-based approach to forensic evaluation. The case featured a complex clinical picture: multiple bone fractures in a child with Infantile Epileptic Spasms Syndrome (West Syndrome), under treatment with valproic acid, and evidence of cocaine exposure. A systematic diagnostic work-up, structured according to authoritative international protocols, was conducted, including detailed medical history, physical examination, imaging, toxicological, and genetic analyses. Despite these compounding challenges, a careful clinical evaluation and critical review of international guidelines led to a definitive diagnosis of child abuse and neglect. This work represents a valuable educational resource for healthcare professionals and underscores the significance of implementing systematic protocols for assessing child maltreatment.